2007
DOI: 10.1007/s10517-007-0219-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compound GB-115 on morphine-induced analgesia

Abstract: Experiments on outbred mice showed that compound GB-115, a retropeptide analogue of the tetrapeptide cholecystokinin, produced a naloxone-dependent potentiating effect on morphine-induced analgesia in the hot-plate test, but did not modulate animal behavior in the tail-flick test in outbred mice. This potentiation of antinociceptive activity of morphine was probably related to the interaction of GB-115 with supraspinal opioidergic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This assumption disagres with our ¿ ndings, because there are strong evidence that afobazole is an agonist of ı 1 -receptors [1,4,6].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This assumption disagres with our ¿ ndings, because there are strong evidence that afobazole is an agonist of ı 1 -receptors [1,4,6].…”
Section: Resultssupporting
confidence: 88%
“…The mechanism of the anxiolytic effect of the preparation is determined by prevention of stress-induced inhibition of binding in the benzodiazepine site of GABA A receptor [5]. At the same time, the interaction of afobazole with ı 1 -receptors was demonstrated [1,4,6]. Apart from CNS, the ı 1 -receptors were identi¿ ed in other organs and tissues of the organism, including the myocardium [12,13].…”
mentioning
confidence: 99%
“…Pharmacological study showed that the dipeptide GB-115 is present in blood plasma after peroral administration and injection [3]. Taking into account the results of previous experiments, GB-115 was administered in doses of 0.1-10 mg/kg [6].…”
Section: Methodsmentioning
confidence: 99%
“…A new dipeptide antagonist of cholecystokinin receptors (GB-115) was synthesized from the endogenous anxiogenic tetrapeptide cholecystokinin-4 (V. V. Zakusov Institute of Pharmacology) [4]. Experiments on mice and rats demonstrated antinociceptive and anxiolytic properties of GB-115 [6]. Taking into account the multicomponent effects of regulatory peptides, we can hypothesize that glycine-containing dipeptide GB-115 exhibits immunocorrecting activity.…”
mentioning
confidence: 99%
“…Anxiolytic and antinociceptive effects of the compound were demonstrated in in vivo experiments [5,6]. Immunocorrective effects of GB-115 was detected in secondary immunodeficiency induced by cyclophosphamide injection [10].…”
mentioning
confidence: 97%